THE POLICY OF "CLEANING" THE PARTY RANKS OF THE BOLSHEVIKS IN UZBEKISTAN AND ITS CONSEQUENCES (American Journal of Research in Humanities and Social Sciences, 2024)
The article examines the policy of "cleansing" the party ranks of the Bolsheviks during the Soviet rule in Uzbekistan and its consequences. The author explained that during the period of Soviet rule, the Center distrusted the activities of national political leaders, unjustified interference in their work, and the fact that they were under strong control.